Effect of rice husk biochar application on rice yield, methane emission and soil carbon sequestration in paddy growing Ultisol - K., RAJALEKSHMI; BASTIN, BETTY (Journal of Soil and Water Conservation, 2021)
Soil health emphasizes the integration of physical, chemical and biological measures of soil quality that affect farmers profit and the environment. Recently, biochar is recognized as soil amendment in agriculture though the technology still remains underutilized. Biochar application is an effective option for promoting soil carbon sequestration, a component in soil quality. Rice husk biochar (RHB) produced from pyrolysis of rice husk (RH) is characterized by a higher nutrient content as compared to wood-derived biochar. A field study was conducted to evaluate the short-term effects of translocation and distribution of RHBderived nutrients in rice crop and their effects on soil nutrients, rice productivity and methane (CH4) emission in paddy growing Ultisol. The treatments included fertilization with four organic sources [farm yard manure (FYM), jack tree (Artocarpus heterophyllus) leaves, daincha (Sesbania aculeata) and rice husk biochar along with a control (no organic manure)] in combination with inorganic nitrogen applied @ 35 (N1), 70 (N2) and 105 (N3) kg N ha-1 through urea. The results showed that the RHB application improved the short-term soil organic carbon (SOC) gain and rice grain and straw yield. The brown rice yield increased with higher N application rates. RHB supplied significant amounts of C to the paddy soil which was recalcitrant and this increased the soil carbon content after rice cultivation. This in turn had significant effect in reducing 50- 60% CH4 emission from soil compared to FYM.